2021
DOI: 10.1016/j.ebiom.2021.103293
|View full text |Cite
|
Sign up to set email alerts
|

Short chain fatty acids and its producing organisms: An overlooked therapy for IBD?

Abstract: The gut microbiome and the intestinal immune system are driving contributors to inflammatory bowel diseases (IBD). Both have an important signalling factor in common: short-chain fatty acids (SCFAs). SCFAs (acetate, propionate and butyrate) are produced by bacterial fermentation in the gut and exert several effects on host metabolism and immune system. This review provides an overview of the current knowledge of these effects, with specific focus on energy metabolism, intestinal barrier, immune system, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
261
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(328 citation statements)
references
References 81 publications
6
261
0
Order By: Relevance
“…Clostridiales are robust producers of short-chain fatty acids (SCFAs), which are fermentation products of anaerobic bacterial metabolism. Higher SCFA gut levels have been associated with positive effects on host metabolism and the health of the gut epithelium, and are known to modulate mucosal immunity ( 45 49 ). For example, SCFAs downregulate LPS-induced proinflammatory mediators, including IL-6, by inhibiting histone deacetylation activity in gut macrophages ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clostridiales are robust producers of short-chain fatty acids (SCFAs), which are fermentation products of anaerobic bacterial metabolism. Higher SCFA gut levels have been associated with positive effects on host metabolism and the health of the gut epithelium, and are known to modulate mucosal immunity ( 45 49 ). For example, SCFAs downregulate LPS-induced proinflammatory mediators, including IL-6, by inhibiting histone deacetylation activity in gut macrophages ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…SCFA‐producing gut bacteria is regarded as the key species for the resistant starch degradation in the human colon; SCFAs, mainly composed of acetate, propionate and butyrate, are beneficial for gut immune integrity; for example, they promote intestinal health, create an environment resistant to pathogenic bacteria and protect against colitis 34,35 . Butyrate, a vital SCFA mainly produced from the Firmicutes genera, was observed to exert crucial anti‐inflammatory effects, reduce oxidative stress, and maintain the integrity of the gut epithelial barrier, particularly in colon 35 . One of most common AGIs, acarbose, augmented colonic butyrate production through the upregulation of butyrate‐producing bacteria in vitro, 36 but the F/B ratio was not significantly affected with acarbose use in the mouse model 4 .…”
Section: Discussionmentioning
confidence: 99%
“…NOD2 mutations influence the abundance of mucosal-adherent bacteria [21] and the transcription of anti-inflammatory cytokine IL-10 [22]. Many studies found that patients with inflammatory bowel disease have fewer SCFA-producing bacteria in their gut, especially Faecalibacterium prausnitzii, a symbiotic bacterium with well-documented beneficial effects for the host [23,24]. Some patients with inflammatory bowel disease, including Crohn's disease and pouchitis, experience clinical improvement with prolonged courses of antibiotics [25,26], while probiotics such as Escherichia coli Nissle 1917 have shown promise in the treatment of pouchitis and the maintenance of remission in ulcerative colitis [27,28].…”
Section: The Microbiome In Inflammatory Bowel Diseasementioning
confidence: 99%
“…NOD2 mutations influence the abundance of mucosal-adherent bacteria [ 21 ] and the transcription of anti-inflammatory cytokine IL-10 [ 22 ]. Many studies found that patients with inflammatory bowel disease have fewer SCFA-producing bacteria in their gut, especially Faecalibacterium prausnitzii , a symbiotic bacterium with well-documented beneficial effects for the host [ 23 , 24 ].…”
Section: The Microbiome In Inflammatory Bowel Diseasementioning
confidence: 99%